Adaptive Modeling to Inform Environmental Management - Katie Irving; Rupert Mathwin; Christopher J. Kotalik; J. Angus Webb; David M. Walters; Siwan Lovett; S. Kyle McKay; Christa L. Torrens; John R. Olson; Ziad A. El Jack (Environmental Management, 2026)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Manipulating water for amphibian conservation - Rupert Mathwin; Skye Wassens; Jeanne Young; Qifeng Ye; Corey J. A. Bradshaw (Conservation Biology, 2021)
Amphibian populations globally are in decline. One great threat is the abstraction of water resources that alter surface‐water hydrology. Conservation actions aimed at restoring or manipulating surface water are employed as a management tool, but empirical evidence on the effectiveness of these approaches is scarce. In this systematic review, we summarized the global experience of manipulating water for amphibian conservation. We explored examples of manipulating water to conserve amphibian species and communities. Approaches varied in their frequency of implementation and in their success. Extending hydroperiod to match larval requirements showed encouraging results, as did off‐season drying to control predators. Spraying water into the environment showed several potential applications, but successes were limited. Despite some promising interventions, we identified few (n = 17) empirically supported examples of successful water manipulation to benefit amphibians. It is unclear whether this stems from publication bias or if it is an artifact of language selection. However, manipulating water shows some potential in amphibian conservation, particularly at sites with a proximal water source and in regions where aridity is increasing due to climate change. Regardless of the scale of the intervention or its perceived probability of success, high‐quality reporting of empirical results will further understanding of how water manipulations can benefit threatened amphibian populations.